OPERATIVE TREATMENT METHODS FOR HUMERUS FRACTURES, BIOS ADVANTAGE - Ashirov Mavlon Umirzakovich (European Science Publishing, 2025)
Humerus fractures are a common orthopedic injury that can significantly impact a patient's quality of life. Various operative treatment methods are available to address these fractures, with the choice of approach often influenced by factors such as fracture type, patient characteristics, and surgeon preference. This article focuses on the operative treatment methods for humerus fractures, with a specific emphasis on the use of biodegradable intramedullary nails (BIOS) as a preferred treatment option. Considerations for selecting BIOS as a treatment method, including patient outcomes, complication rates, and surgical techniques, are discussed. Overall, this article provides insights into the role of BIOS in the operative management of humerus fractures and offers guidance for clinicians in selecting appropriate treatment methods based on individual patient needs and preferences.
Keywords: Humerus fractures, operative treatment methods, biodegradable intramedullary nails (BIOS), BIOS preference, orthopedic surgery, fracture management